Gender Equality in the Criminal Justice System in Dubai: Between Sharia and Human Rights - Mustafa, Cecep; Komalasari, Rita (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This paper explores the distinctive fusion of tradition and modernity in Dubai and offers an engaging context for analyzing the ways in which the criminal justice system responds to the difficulties presented by the coexistence of Sharia law and human rights ideals. With a focus on minority rights and gender problems, the research seeks to give a thorough knowledge of how the cohabitation of Sharia law and human rights impacts justice, equality, and respect for human rights. The research aims to clarify the difficulties present in this legal environment and provides suggestions for future improvements through a targeted examination. The study critically examines legal provisions, precedents, and practical implementations, utilizing legal pluralism as a theoretical framework to understand the interplay between Sharia law and human rights principles. Insights from stakeholder and legal expert interviews are also incorporated into the analysis to provide viewpoints from inside the criminal justice system. The study highlights both advancements and difficulties in providing a detailed knowledge of gender relations within the criminal justice system. The study ends with a critical analysis of the implications for policy and possible changes, adding to the continuing conversation about justice, equality, and human rights in Dubai's developing legal system.